Internationalistinnen : sechs Lebensbilder - Schwarz, Helga 1938- (Kleine Militärgeschichte: Biografien, 1989)
Frida Rubiner, Elisabeth Saborowski-Ewert, Maria Leitner, Larissa Reisner, Rosa Jochmann, Helene Rado-Jansen